2017
DOI: 10.3389/fphar.2017.00545
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Improves Mitochondrial Function in the Remnant Kidney and Protects against Renal Fibrosis in 5/6 Nephrectomized Rats

Abstract: Pioglitazone is a type of peroxisome proliferator-activated receptor γ (PPARγ) agonist and has been demonstrated to be effective in chronic kidney diseases (CKD) treatment. However, the underlying mechanism involved in the renoprotection of pioglitazone has not been fully revealed. In the present study, the renoprotective mechanism of pioglitazone was investigated in 5/6 nephrectomized (Nx) rats and TGF-β1-exposed HK-2 cells. Pioglitazone attenuated renal injury and improved renal function, as examined by 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…Decreased amounts of mitochondrial proteins (e.g., acyl-coenzyme A dehydrogenase medium chain, heat shock protein family A member 9, ATP synthase F1 subunit beta, NADH:ubiquinone oxidoreductase subunit B8, and mitochondrially encoded cytochrome c oxidase I), and mitochondrial DNA in the renal tissue of 5/6Nx rats were reported throughout the disease progression. 9,37 In this study, the renal uptake of 18 F-BCPP-BF had already started, albeit mildly, to decrease in the early phase of disease progression, then at the progression phase, the decrease was exacerbated along with the decline of the renal function. Mitochondrial proteins were remarkably decreased in the kidneys of 15-week-old 5/6 Nx rats.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Decreased amounts of mitochondrial proteins (e.g., acyl-coenzyme A dehydrogenase medium chain, heat shock protein family A member 9, ATP synthase F1 subunit beta, NADH:ubiquinone oxidoreductase subunit B8, and mitochondrially encoded cytochrome c oxidase I), and mitochondrial DNA in the renal tissue of 5/6Nx rats were reported throughout the disease progression. 9,37 In this study, the renal uptake of 18 F-BCPP-BF had already started, albeit mildly, to decrease in the early phase of disease progression, then at the progression phase, the decrease was exacerbated along with the decline of the renal function. Mitochondrial proteins were remarkably decreased in the kidneys of 15-week-old 5/6 Nx rats.…”
Section: Discussionmentioning
confidence: 52%
“…One direct method is to measure the oxygen consumption rate of isolated mitochondria. [9][10][11] However, the complicated process of mitochondrial isolation may cause data variation. The mitochondrial morphology (e.g., fragmentation or hyperfusion) is a widely accepted indicator of their functional status.…”
mentioning
confidence: 99%
“…Pioglitazone can inhibit pyruvate‐driven ATP synthesis and glucose production in isolated mitochondria from hepatocytes . Further, it can prevent the cytochrome C leakage, stabilize the mitochondrial membrane potential, maintain the ATP production, inhibit the ROS generation and activities the ETC complexes I and III . However, its role in NAFLD has not yet been evaluated.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Brain and heart tissues depend on mitochondria for their high energy consumption and maintenance of their normal function [15,16]. Research has shown that mitochondria are one of the targets of PPARγ agonists [3,17,18]. Mitochondrial dysfunction has been reported by exposure to TZDs.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria as one of the important organelles in eukaryotic cells are involved in important physiological processes including the generation of free radicals, energy production and cell death [2,3,14,19,22]. Therefore, mitochondrial dysfunction can be dangerous for different cells and organs due to insufficient ATP generation and excessive level of ROS [18]. The in vitro cytotoxicity investigations can be helpful in providing mechanistic information, and this information can be useful in understanding the more detailed clinical observations [19].…”
Section: Introductionmentioning
confidence: 99%